Uji Aktivitas Antibakteri Ekstrak Daun Kesambi (Schleichera Oleosa) terhadap Bakteri Propionibacterium Acnes - Dian Arvita Margaretha Maubana; Arley Sadra Telussa; Christina Olly Lada; Magdarita Riwu (Green Publisher Indonesia, 2026)
Propionibacterium acnes is a gram-positive anaerobic bacteria, which is a normal flora found in the skin. However, if there is a blockage of pilosebaceous gland secretion and increased sebum production, it can make Propionibacterium acnes bacteria invasive and potentially cause one of the skin diseases, namely acne. To overcome the problem of acne, treatment with antibiotics can be done. However, based on the results of research, treatment of Propionibacterium acnes with antibiotics has experienced resistance. To overcome this problem, another alternative is needed by using herbal plants that have antibacterial compounds, and one of the plants that has potential as an antibacterial is kesambi leaf (Schleichera oleosa). The purpose of this study was to test the antibacterial activity of kesambi leaf extract (Schleichera oleosa) against Propionibacterium acnes bacteria. The type of research used in this study is Experimental Design with Post Test Only Control Group Design. The treatment groups in this study consisted of concentrations of 60%, 30%, 15%, 7.5%, 3.75%, positive control clindamycin, and negative control sterile aquadest with repetition 4 times in each treatment group. Data analysis using One Way Anova statistical test. The results of testing the antibacterial activity of kesambi leaf extract against Propionibacterium acnes bacteria show that the extract has antibacterial activity. Dataanalysis with One Way Anova test obtained p < 0.001 smaller than a = 0.05 which means there is a significant difference in the average diameter ofthe inhibition zone. Kesambi leaf extract (Schleichera oleosa) has antibacterial activity against the growth of Propionibacterium acnes bacteria